2014
DOI: 10.1177/1535370214562338
|View full text |Cite
|
Sign up to set email alerts
|

Protective phenotypes of club cells and alveolar macrophages are favored as part of endotoxin-mediated prevention of asthma

Abstract: Atopic asthma is a chronic allergic disease that involves T-helper type 2 (Th2)-inflammation and airway remodeling. Bronchiolar club cells (CC) and alveolar macrophages (AM) are sentinel cells of airway barrier against inhaled injuries, where allergy induces mucous metaplasia of CC and the alternative activation of AM, which compromise host defense mechanisms and amplify Th2-inflammation. As there is evidence that high levels of environmental endotoxin modulates asthma, the goal of this study was to evaluate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
2
16
1
Order By: Relevance
“…As was shown before (55), the OVA-allergic inflammation incited mucous cell metaplasia in the bronchiolar Club cell via EGFR signaling. In this way, Figure 3 shows an increased number of mucous secreting cells (AB-PAS panel in Fig 3a and Fig.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…As was shown before (55), the OVA-allergic inflammation incited mucous cell metaplasia in the bronchiolar Club cell via EGFR signaling. In this way, Figure 3 shows an increased number of mucous secreting cells (AB-PAS panel in Fig 3a and Fig.…”
Section: Resultssupporting
confidence: 70%
“…Next, we analyzed whether the mucous metaplasia prevention by neonatal LPS treatment correlated with changes in the expression of epithelial host defense mediators, mainly CCSP and SP-D. As it was described (55), OVA-allergic inflammation induced a diminution in the imunoreactivity of CCSP and SP-D in CC of PBSn/OVA group when compared to its control group (CCSP and SP-D panels in Fig 5a). Meanwhile for both LPSn and LPSn/OVA groups, a strong CCSP and SP-D immunolabelling was observed (Fig 5a).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…61 Previous studies have demonstrated that lipopolysaccharide (LPS) pre-exposition modified the local bronchioalveolar microenvironment by promoting features of M1 macrophages that express nitric oxide, while avoiding M2 macrophage expression of arginase-1 and reducing local factors that drive Th2 type responses, thereby suppressing allergic inflammation. 62 By quantifying the lung macrophage populations in two established murine models of allergic and non-allergic lung inflammation, data showed that M2 macrophages predominantly localized in the lungs in allergic asthma, while M1-dominant macrophages were more prevalent in non-allergic inflammation, which may contribute to Th1/Th17 responses via the transcription factor interferon-regulatory factor 5 (IRF5). Thus, interfering with this polarization may potentially lead to the treatment of different types of lung inflammation.…”
Section: Introductionmentioning
confidence: 99%